The development of the North–South International Multimodal Transport Corridor and the measures to integrate the regional transport infrastructure - M. I. Malyshev; E. N. Kozhanov (Научный вестник МГТУ ГА)
The problems of the North–South Transport Corridor development are directly interrelated with the integration of the regional infrastructure of the countries participating in this project. The importance of this corridor currently affects not only the economic sphere, but also the geopolitics of the world community as a whole, as the power balancing issues in the world economy are engaged. Based on the results of the statistical data study from open sources, the analysis of extensive periodical literature, the pros and cons of the North–South Multimodal Transport Corridor (MTC) project are substantiated, and the promising ways of implementing and improving its effectiveness are identified. Political pressure on a number of participating countries and an asymmetry of interests are highlighted as factors that hinder the active implementation of the project (the most interested participants are Iran and Russia, other parties may have negative geopolitical and economic consequences from participating in the project). There are major challenges concerning the infrastructure development and the insufficient degree of harmonization of the institutional conditions within which the transport corridor operates. On the other hand, the greatest advantages of the North–South Transport Corridor are reducing dependence on other transport routes, including those passing through competitive countries, increasing national security and sovereignty of Russia, consolidating Eurasian integration, improving foreign policy links with the countries in Asia and Africa. In order to maximize the potential of the North–South MTC and increase its competitiveness in comparison with other transport hubs, the following ways are proposed: 1. One-time solution to a set of tasks: modernization of infrastructure, primarily, port infrastructure in Russia, railway infrastructure in Iran; full digitalization of the transport and logistics sphere in all the participating countries; harmonization of institutional conditions for the project implementation in the domain of legislation, customs procedures, business processes, management. 2. More active use of free economic zones and special economic zones. 3. Formation of a special supranational organizational structure that will directly deal with the development of the North– South International Transport Corridor.